Testing the method of measuring of kinesiophobia on patients with movement disorders - A.V. Kotel'nikova; A.А. Kukshina (Экспериментальная психология, 2018)
The aim of this study was to conduct the procedure of psychometric adaptation the Russian version of the questionnaire «Scale Tampa» for measuring of kinesiophobia (fear of movement). On the representative sample of the patients (n=292) with movement disorders of various etiologies studied factorial structure and nosological nonspecificity of method, showed its satisfactory construct and discriminative validity, analyzed the influence of social desirability factor, estimated synchronous reliability of selected subscales. Separately analyzed pharmaco-economic value of the test construct. Thus, it is shown that a sufficiently high psychometric indicators allow to use a questionnaire «Tampa Scale» as for scientific and research purposes, as in the practical work of clinical psychologist.